(3GdeGdjI GdYGeI (B/s - (3GdMGL , WGQb, s ((3YeGf(B: s (3OGQ UaGA(B, s, 2009)
(3eONd Gdi GdeGdjI GdYGeI h JfGhd GdeGdjI GdYGeI aj GdGfXeI GdeNJdaI eY GdJWQb Gdi GdGjQGOGJ GdYGeI h GdGjQGOGJ ef GdVQGFH h cPG GdVQGFH Ydi GdONd h Ydi QCS GdeGd h Ydi GdCfaGb eY WQb JbOjQ GdeGOI GdNGVYI ddVQjHI h MSGH GdVQjHI h GdJgQH ef GdVQGFH h GdGYaGAGJ GdVQjHjI h GdGfYcGS GdVQjHj h BKGQ GdVQGFH h cPG JfGhd GdGjQGOGJ ef GdQShe h ef GdbQhV h GdfabGJ GdYGeI h GdehGRfI GdYGeI h CNjQG GdSjGSI GdeGdjI h GdSjGSI GdfbOjI(B.s
(3eQGLY U(B.224s
Keywords: (3GdVQGFHs; (3GdeGdjI GdYGeIs; (3GdfabGJ GdYGeIs